2005
DOI: 10.1042/bst0331405
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of Toll/interleukin-1 signalling networks by expression cloning

Abstract: Multiple cellular proteins have been identified as participating in Toll/interleukin-1 receptor-mediated inflammatory gene expression. The continuing isolation of novel components, based on sequence similarities, protein-protein interactions and protein purification, suggests that many elements of this signalling network remain to be identified. We report here the development of a high-throughput functional screening platform and its application for the identification of components of inflammatory signalling n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…TRIB3 proteins appear to act as activators and inhibitors of MAPK activity, depending on the ratio of TRIB3 to MAPKK in the cell. In mammalian cells, TRIB3 at a relatively low level can activate MAPK phosphorylation, especially ERK1/2 phosphorylation (25,26). Interestingly, overexpression of TRIB3 decreased insulin-stimulated ERK1/2 phosphorylation in muscle cells but increased ERK1/2 phosphorylation under basal conditions in our experiments.…”
Section: E571 Trib3 Impairs Insulin Action In Skeletal Musclementioning
confidence: 47%
“…TRIB3 proteins appear to act as activators and inhibitors of MAPK activity, depending on the ratio of TRIB3 to MAPKK in the cell. In mammalian cells, TRIB3 at a relatively low level can activate MAPK phosphorylation, especially ERK1/2 phosphorylation (25,26). Interestingly, overexpression of TRIB3 decreased insulin-stimulated ERK1/2 phosphorylation in muscle cells but increased ERK1/2 phosphorylation under basal conditions in our experiments.…”
Section: E571 Trib3 Impairs Insulin Action In Skeletal Musclementioning
confidence: 47%
“…However, the biological relevance of this interaction is still unknown as there has been no independent confirmation and further characterisation of trb-1/12-LOX binding. Our group have reported recently the identification of human tribbles-1 as a novel regulator of AP-1 activation in a screen [9], which is designed to rapidly annotate signalling network components based on their function [13][14][15]. Further characterisation of trb-1 function revealed that this protein (similarly to trb-3) binds to the 'middle layer' of kinases in the MAPK network, the MAPKKs [16].…”
Section: Mammalian Tribblesmentioning
confidence: 98%
“…Using a genome-wide functional screen for components of inflammatory signalling networks, we identified a novel protein, human homologue of Drosophila tribbles (trb) [44,45] that is critically required for regulation of IL-8 expression in HeLa cells. A subsequent database search revealed the existence of three mammalian tribbles-like proteins (Htrb1, 2 and 3) and we have shown that these selectively regulate the activation of ERKs, JNKs and p38 MAPK by interacting with MAP kinase kinases (MAPKKs) in a specific manner that regulates their activity [46].…”
Section: Introductionmentioning
confidence: 99%